Quantitative Analysis and Comparison of Flavonoids in Lotus Plumules of Four Representative Lotus Cultivars - Ting Liu; Mingzhi Zhu; Chunyun Zhang; Mingquan Guo (Journal of Spectroscopy)
The flavonoids in lotus plumules from four representative lotus cultivars have been analyzed using high-performance liquid chromatography coupled with ultraviolet detector and electrospray ionization triple quadrupole mass spectrometry. By this means, sixteen flavonoids were successfully measured and compared among four cultivars. Although similar flavonoid compositions were detected from these four cultivars, their flavonoid contents were significantly different. cv. Bailian from Guangchang was detected to have the most total flavonoid content, that is, 1595.86 mg/100 g, followed by cv. Xuanlian from Wuyi (1553.49 mg/100 g), cv. Xianglian from Xiangtan (1173.07 mg/100 g), and cv. Jianlian from Jianning (930.08 mg/100 g). However, similar percentages of flavonoid C-glycosides in the total flavonoids were found for four cultivars, which were 80.83% for cv. Bailian, 80.91% for cv. Xianglian, 79.25% for cv. Jianlian, and 78.53% for cv. Xuanlian. This work will be very useful for quality assurance and control for the lotus plumules from different origins in terms of qualitative and quantitative information about flavonoids. It will also be of special interest in the screening of lotus plumules with high flavonoid content, which are preferred due to their wide potential applications in food and pharmaceutical industries.